2019
DOI: 10.1083/jcb.201812135
|View full text |Cite
|
Sign up to set email alerts
|

CHC22 clathrin mediates traffic from early secretory compartments for human GLUT4 pathway biogenesis

Abstract: Glucose transporter 4 (GLUT4) is sequestered inside muscle and fat and then released by vesicle traffic to the cell surface in response to postprandial insulin for blood glucose clearance. Here, we map the biogenesis of this GLUT4 traffic pathway in humans, which involves clathrin isoform CHC22. We observe that GLUT4 transits through the early secretory pathway more slowly than the constitutively secreted GLUT1 transporter and localize CHC22 to the ER-to-Golgi intermediate compartment (ERGIC). CHC22 functions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(87 citation statements)
references
References 79 publications
(162 reference statements)
10
77
0
Order By: Relevance
“…Full-size  DOI: 10.7717/peerj.8751/ fig-5 While both the overlap with ERGIC53 and the GLUT4/DAPI ratio were decreased upon Sx6 knockdown, these did not reach significance (p~0.06 in both cases). This may reflect the relative capacity of the GOSR1/YKT6 pathway compared to the Sx6/Sx16 pathway in different cell types (Camus et al, 2020). These caveats notwithstanding, our data point to a role for the SNAREs GOSR1 and YKT6 in GLUT4 trafficking in human cells.…”
Section: Identification Of New Components Of Glut4 Traffickingmentioning
confidence: 59%
See 4 more Smart Citations
“…Full-size  DOI: 10.7717/peerj.8751/ fig-5 While both the overlap with ERGIC53 and the GLUT4/DAPI ratio were decreased upon Sx6 knockdown, these did not reach significance (p~0.06 in both cases). This may reflect the relative capacity of the GOSR1/YKT6 pathway compared to the Sx6/Sx16 pathway in different cell types (Camus et al, 2020). These caveats notwithstanding, our data point to a role for the SNAREs GOSR1 and YKT6 in GLUT4 trafficking in human cells.…”
Section: Identification Of New Components Of Glut4 Traffickingmentioning
confidence: 59%
“…The relative balance of different endosomal pathways may differ between these cell types and thus reveal different facets of GLUT4 trafficking. Consistent with this, studies have suggested that GLUT4 trafficking differs between human and murine cells (Camus et al, 2020), and hence some distinctions between these two cell systems are not entirely unsurprising.…”
Section: Common Trafficking Pathways For Glut4 In Hela and 3t3-l1 Adimentioning
confidence: 63%
See 3 more Smart Citations